2018
DOI: 10.3390/cancers10030082
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Protein Tyrosine Phosphatases in Hepatocellular Carcinoma

Abstract: The protein tyrosine phosphatase (PTP) family is involved in multiple cellular functions and plays an important role in various pathological and physiological processes. In many chronic diseases, for example cancer, PTP is a potential therapeutic target for cancer treatment. In the last two decades, dozens of PTP inhibitors which specifically target individual PTP molecules were developed as therapeutic agents. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors and is the second most let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 177 publications
(221 reference statements)
1
46
0
Order By: Relevance
“…PRL-1-This phosphatase causes activation of AKT, and inhibition of GSK3β, consequently, contributes for elevated levels of Snail expression and decreased Ecadherin expression. In agreement, the high level of this enzyme was associated with more aggressive phenotype and poorer prognosis in hepatocellular carcinoma patients [46].…”
Section: Ptps Contribute For Metastasis Through Extracellular Matrix supporting
confidence: 64%
See 2 more Smart Citations
“…PRL-1-This phosphatase causes activation of AKT, and inhibition of GSK3β, consequently, contributes for elevated levels of Snail expression and decreased Ecadherin expression. In agreement, the high level of this enzyme was associated with more aggressive phenotype and poorer prognosis in hepatocellular carcinoma patients [46].…”
Section: Ptps Contribute For Metastasis Through Extracellular Matrix supporting
confidence: 64%
“…PRL-3-PRL-3 activates the PI3K/PKB pathway and promotes EMT by decreasing PTEN protein expression [23]. In addition, it was demonstrated that expression of PRL-3 in hepatocellular carcinoma patients was positively correlated with the expression of MMPs 1, 9, 10, and 12 [46].…”
Section: Ptps Contribute For Metastasis Through Extracellular Matrix mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC), accounting for nearly 90% of liver cancer, is the main form of liver cancer [2,3]. Due to its poor early diagnosis and limited therapy methods, HCC is the most lethal malignant cancer worldwide [4]. Generally, the 5-year overall survival rate of HCC patients is still low [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that deregulation of phosphatases contributes to tumorigenesis and progression of HCC [3][4] . Because of the relative feasibility of developing small molecule inhibitors to block phosphatases 5 , studies focus on the role of such phosphatases may provide clinical significance for the management of HCC. Our previous studies have reported a series of phosphatases that play important roles in HCC.…”
Section: Introductionmentioning
confidence: 99%